2002
DOI: 10.1046/j.1523-1755.2002.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapies in the aftermath of the catastrophic Marmara earthquake

Abstract: Substantial amounts of dialysis support may be necessary for treating the victims of mass disasters complicated with crush syndrome. Dialyzed patients are characterized by higher rates of morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The relation between QOL and metabolic control is controversial [13,[41][42][43][44]. Some studies reported an association between QOL and metabolic control [41,42], whereas others found no association [13,43,44]. This study confirmed previous studies reporting that no association was found between glycemic control and QOL in type 1 diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The relation between QOL and metabolic control is controversial [13,[41][42][43][44]. Some studies reported an association between QOL and metabolic control [41,42], whereas others found no association [13,43,44]. This study confirmed previous studies reporting that no association was found between glycemic control and QOL in type 1 diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…The DQOL is a disease-specific measure designed specifically for use in DCCT but with applicability to a wider range of people with type 1 diabetes [32]. The relation between QOL and metabolic control is controversial [13,[41][42][43][44]. Some studies reported an association between QOL and metabolic control [41,42], whereas others found no association [13,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, energetic fluid administration prevents crush syndrome. After the Bingol-Turkey earthquake in 2003, early fluid resuscitation was associated with a lower percentage of crush cases requiring dialysis (11) than in other contemporaneous disasters (12,13). Similarly, in the recent Haiti earthquake, dialysis could be avoided in several victims because of intensive fluid administration (14).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of standard haemodialysis equipment, supplies and trained personnel; unreliable and/or unsafe water sources; and non-functional or unreliable electrical systems, are some of the factors that limit the ability to care for victims with renal failure requiring renal replacement therapy. Man-made or natural disasters, such as the 1999 Marmara earthquake in Turkey, may threaten to overwhelm existing local dialytic resources, if they remain functional at all [2]. The challenge is not limited to disasters in which patients develop de novo renal failure; the chronic dialysis population itself may require the immediate implementation of alternative renal replacement therapies if patients are unable to access haemodialysis centres or hospitals, as observed during the flooding of New Orleans in the aftermath of Hurricane Katrina in 2005 [3].…”
Section: Introductionmentioning
confidence: 99%